Recension de Jonathon Glassman, 2011,"War of Words, War of Stones. Racial Thought and Violence in Colonial Zanzibar", Bloomington, Indiana Univ. Press. - (:unkn) unknown (My University, 2013)
Writing the history of a place, Zanzibar, where contentious and competing distortions of the past are pervasive today, where facts are reinvented to fit contemporary needs and claims, and where homespun nationalist history has long prevailed over the history of academic historians, is not an easy task. Jonathan Glassman proves up to it, though his work may not please local amateur historians. In War of Words, War of Stones, the author, a historian at Northwestern University who was much applauded for a previous book about rebellion and violence on the Swahili coast of Eastern Africa, aims to explain the birth of racial thought in Zanzibar in the 1950s and its violent impact on the population of this tiny Indian Ocean archipelago off the East African coast, today part of Tanzania.....
Keywords: African Research